Radiobiological aspects of intraoperative radiotherapy (IORT) with isotropic low-energy X rays for early-stage breast cancer - Herskind, Carsten; Steil, Volker; Kraus-Tiefenbacher, Uta; Wenz, Frederik (Radiation research, 2005)
The purpose of this study was to model the distribution of biological effect around a miniature isotropic X-ray source incorporating spherical applicators for single-dose or hypofractionated partial-breast intraoperative radiotherapy. A modification of the linear-quadratic formalism was used to calculate the relative biological effectiveness (RBE) of 50 kV X rays as a function of dose and irradiation time for late-reacting normal tissue and tumor cells. The response was modeled as a function of distance in the tissue based on the distribution of equivalent dose and published dose-response data for pneumonitis and subcutaneous fibrosis after singledose conventional irradiation. Furthermore, the spatial distribution of tumor cell inactivation was assessed. The RBE for late reactions approached unity at the applicator surface but increased as the absorbed dose decreased with increasing distance from the applicator surface. The ED50 for pneumonitis was estimated to be reached at a depth of 6-11 mm in the tissue and that for subcutaneous fibrosis at 3-6 mm, depending on the applicator diameter and whether the effect of recovery was included. Thus lung tissue would be spared because of the thickness of the thorax wall. The RBE for tumor cells was higher than for late-reacting tissue. The applicator diameter is an important parameter in determining the range of tumor cell control in the irradiated tumor bed. (C) 2005 by Radiation Research Society.